The Problem of Readers' Perception of “Difficult” Literary Texts - Sarvinoz Yashinovna Eshonqulova (Web of Journals Publishing, 2023)
The paper is devoted to consideration a problem of reading as important cultural and didactic phenomenon. The different types of reader’s perception of modern fiction literature are characterized, which allows the author to reveal features of the reading of the difficult Russian postmodern texts. The conclusions are interpreted in the framework of didactic intents.
Keywords: Aesthetic resonance, reader's intention, reader-researcher, critical-skeptical perception, abstract-logical perception.